Cooperative Learning on The Academic Achievement of Middle-School Students Based on Learning Style - Arifin, Kurniati (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The goals of this study are to (1) see if students who are taught using the Teams Assisted Individualization (TAI) cooperative learning model learn mathematics better than students who are taught using the Student Team Achievement Division (STAD) model, and (2) see if the results of learning mathematics with visual learning styles are better than those with auditory and kinesthetic learning styles. As a result, this sort of study is an experiment. The experimental class I was class VIII students from Public Junior High School 1 North Sinjai. The findings revealed that: (1) students who were taught using the TAI type had better mathematics learning outcomes than students who were taught using the STAD type; (2) the inferential analysis revealed that it was not true that students with visual learning styles had better mathematics learning outcomes than students with auditory and kinesthetic learning styles.